Transnationals Becoming English Teachers in Mexico: Effects of Language Brokering and Identity Formation (GIST – Education and Learning Research Journal, 2015)
The objective of this research was to explore the effects of language brokering upon identity formation within the family unit of students who have lived in the United States for a period of time and have come back to live in Mexico. The participants are six students that are currently undertaking a BA in TESOL (Teaching of English to Speakers of Other Languages) at a large public university in central Mexico. Findings from interviews, following a narrative approach, seem to show that these participants’ experiences as language brokers are highly valuable when they decide to become English teachers. Most of them decide to become English teachers because they want to help others to learn the language and bring those experiences into the classroom.
Keywords: Language brokering; identity construction; narrative inquiry; transnational